Operations management: Nineth Edition - William J. Stevenson (Mc .Grow-Hill, 2002)
File dalam bentuk Gambar,Video, Htm (Internet), dll; Isi: AVI, Data-Sets, Help, Outline, Ppt, Quizzes, Schedule, Simplex, Template, Transportation, Viewer, Weblink,, dll; Judul dalam kemasan.